Understanding the patterns and drivers of domestic violence against women in Birnin Kebbi Nigeria - Sanusi Naja’atu Baura; Abdulmumin Musa Omiya (An-Nisa’ Journal of Gender Studies, 2025)
Domestic violence against women in Birnin Kebbi remains a persistent social problem, reflecting complex dynamics shaped by power imbalances, patriarchal norms, and family structures. Acts of physical, sexual, verbal, emotional, and economic violence not only harm victims but also undermine social well-being, indicating an urgent need for context-sensitive prevention strategies and empowerment-based interventions. The objective of this study is to analyze the prevalence, forms, and women’s perceptions of domestic violence in Birnin Kebbi LGA, while also exploring the socio-demographic, economic, and cultural factors that influence vulnerability to violence. This research employs a quantitative survey involving 259 married women in Birnin Kebbi, combining multi-stage random sampling and purposive sampling techniques. Data were collected through structured questionnaires and analyzed using descriptive and comparative methods. Validity, reliability, and confidentiality were ensured throughout the research process. The findings indicate a very high prevalence of domestic violence in Birnin Kebbi Metropolis (61.83%), with physical violence (25.1%) and economic violence (23.72%) being the most dominant forms. Cultural normalization is evident, as 41.99% of respondents perceive wife beating as a form of discipline and uphold the belief in the husband's absolute sexual rights. Low levels of education and women's economic dependency further exacerbate victims' vulnerability. This study concludes that domestic violence in Birnin Kebbi is systemic and multidimensional, rooted in power imbalances, patriarchy, and socioeconomic inequalities that perpetuate cycles of violence. This study contributes to strengthening domestic violence theory by identifying education and economic dependency as mediating mechanisms, while also proposing multidimensional interventions.